(untitled) (Research, Society and Development, 2021)
Pebble mining operations in the municipality of Ourém begin with deforestation, clearing, excavation, loading, transport and restoration of mined areas. The objective of this work is to recommend the use of pre-selected native forest species with ecological characteristics to favor the rapid recovery of an environmental area degraded by the removal of pebbles. The data collection procedure was planned according to the general and specific objectives of the research, with data collection being carried out from secondary and primary sources. The road was used as a path to cover a length of 3 km to carry out the forestry diagnosis. Forest identification was carried out by observing adult individuals on both sides of the road. The list of species acquired in the mining company’s area can help in the recovery of areas altered by pebble mining activities in the municipality of Ourém – PA and other areas with similar characteristics. The numerous presence of sun-tolerant families and pioneer species demonstrates the floristic diversity of this environment and the quality of the site. Typical species from Amazonian tropical forests such as Bertholletia excelsa Humb were recorded. & Bonpl, Aniba rosaeodora Ducke and Vouacapoua americana Aubl., demonstrating that we need to revegetate degraded ecosystems.